Non-stick pan composite coating and preparation method thereof
By sandblasting the non-stick pan substrate and mixing the polytetrafluoroethylene powder with modified carbon nanotubes, a composite resin coating was prepared, which solved the problem of early non-stick pan coating failure due to mechanical damage, and achieved higher non-stick properties and wear resistance.
Patent Information
- Application Number
- CN202411756828.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
AI Technical Summary
Early non-stick pan coating failed due to mechanical damage, resulting in a shortened service life and urgently needed improvement.
The inner surface of the non-stick pot substrate was sandblasted and coarsed by porous ceramic particles, and the polytetrafluoroethylene powder was mixed with modified carbon nanotubes, and the activated composite powder was mixed with fluorosilicone resin using a silane coupling agent to prepare the composite resin and coated on the inner surface of the non-stick pot substrate to cure.
It improves the non-stick performance and wear resistance of the coating and extends the service life of the non-stick pan.
Smart Images

Figure BDA0005166514920000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of non-stick pan coatings, and in particular to a non-stick pan composite coating and a preparation method thereof. Background Art
[0002] In the development history of modern kitchen utensils, non-stick pans have gradually become the darling of consumers due to their unique performance advantages. The key to the performance of non-stick pans lies in their surface coating. By forming a non-stick coating on the surface of the pan, the pan can prevent food from sticking to the inner wall of the pan during cooking, which not only improves cooking efficiency but also makes cleaning easier.
[0003] Early non-stick pans mainly relied on pure polytetrafluoroethylene coatings, in which fluorine atoms and carbon atoms formed extremely strong covalent bonds, which could form a dense barrier after the inner wall of the non-stick pan was formed. The coating surface has extremely low surface energy, which can effectively prevent food from adhering. However, as the polytetrafluoroethylene coating is used for a long time, it is easy to fail due to mechanical damage, which greatly affects the service life of the non-stick pan coating. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0004] In view of this, the present invention provides a non-stick pan composite coating and a preparation method thereof to solve the above problems.
[0005] The technical solution of the present invention is achieved as follows: a method for preparing a non-stick pan composite coating comprises the following steps:
[0006] S1. The inner surface of the non-stick pan substrate is roughened by sandblasting using porous ceramic particles, and then degreased and cleaned.
[0007] S2. Mixing polytetrafluoroethylene powder and modified carbon nanotubes and grinding them to obtain composite powder.
[0008] S3. Activate the composite powder using a silane coupling agent, add the activated composite powder into a fluorosilicone resin and mix to obtain a composite resin.
[0009] S4, coating the composite resin on the inner surface of the non-stick pan substrate and curing it to obtain a non-stick pan composite coating.
[0010] Further, the porous ceramic particles in S1 are prepared by the following method: kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, sodium hexametaphosphate are mixed, stirred at 500-1000rpm for 10-20min, then placed in a granulator to make a size of 600-800nm, then placed in a drying oven, dried at 100-150℃ for 8-10h, then placed in a sintering furnace, and sintered at 1000-1300℃ for 5-7h. The mass volume ratio of kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate is g / mL (4.0-6.0): (1.0-3.0): (1.0-3.0): (0.5-1.5): (0.1-0.3): (0.1-0.2): (0.03-0.05).
[0011] Furthermore, the modified carbon nanotubes in S2 are prepared by the following method: soaking the carbon nanotubes in tetraethyl orthosilicate, separating and drying to obtain a modified intermediate, and then mixing the modified intermediate with nano-alumina in boiling water, separating and drying to obtain the modified carbon nanotubes.
[0012] Further, the carbon nanotubes are immersed in tetraethyl orthosilicate at 40-60° C. for 20-30 minutes, separated by suction filtration, and dried at 60-80° C. for 4-6 hours to obtain a modified intermediate, wherein the mass volume ratio of the carbon nanotubes to tetraethyl orthosilicate is (0.1-0.5):(1.0-3.0) g / mL.
[0013] Further, the modified intermediate is mixed with nano-alumina, placed in boiling water, boiled in boiling water for 30-40 minutes, then cooled to room temperature, filtered and separated, and dried at 60-80° C. for 4-6 hours to obtain modified carbon nanotubes. The mass volume ratio of the modified intermediate, nano-alumina, and boiling water is 1.0:(0.1-0.2):(2.0-3.0) g / mL.
[0014] Furthermore, the composite powder in S2 is prepared by the following method: polytetrafluoroethylene powder and modified carbon nanotubes are mixed and ground at a mass ratio of 1.0:(0.1-0.2) to obtain the composite powder, wherein the particle size of the composite powder is 100-200 nm, and the polytetrafluoroethylene powder and the modified carbon nanotubes are ball-milled in a non-oxidizing atmosphere.
[0015] Furthermore, the composite resin in S3 is prepared by the following method: the composite powder is put into the silane coupling agent activation solution, ultrasonically mixed for 10-15 minutes at 50-60°C, ultrasonic power 300-500W, and ultrasonic frequency 20-50kHz, and then the composite powder is separated and dried at 60-80°C for 2-4 hours to obtain the activated composite powder. The mass volume ratio of the composite powder to the silane coupling agent activation solution is 1:(2-4) g / mL. The activated composite powder is put into the fluorosilicone resin, a diluent is added, and the mixture is stirred and mixed at 500-1000rpm for 10-20 minutes to obtain the composite resin. The mass volume ratio of the activated composite powder, fluorosilicone resin, and diluent is 1.0:(1.0-1.2):(0.1-0.2) g / mL. The diluent is composed of N,N-dimethylformamide and isopropanol in a volume ratio of (8-9):(1-2).
[0016] Furthermore, the silane coupling agent is one or a combination of γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane, and β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane. The silane coupling agent activation solution is prepared by diluting the silane coupling agent by 4-6 times with deionized water.
[0017] Furthermore, the fluorosilicone resin is polytrifluoropropylmethylsiloxane or polymethyltrifluoropropylsiloxane.
[0018] Furthermore, the curing and molding in S4 is specifically curing and molding at 240-260° C. for 2-3 hours to obtain a non-stick pan composite coating.
[0019] Furthermore, the non-stick pan composite coating prepared by the above-mentioned preparation method of the non-stick pan composite coating has a thickness of 100-200 um.
[0020] Compared with the prior art, the present invention has the following beneficial effects: by modifying the carbon nanotubes, the present invention can improve the dispersion performance of the carbon nanotubes, thereby inhibiting the agglomeration of the carbon nanotubes, allowing the carbon nanotubes to be evenly distributed with the polytetrafluoroethylene powder, avoiding microscopic protrusions and depressions formed by agglomeration, making the coating surface smoother, thereby improving the non-stick performance of the coating. In addition, the modification treatment increases the surface roughness of the carbon nanotubes, thereby increasing the contact area between the carbon nanotubes and the fluorosilicone resin, providing more binding sites, thereby enhancing the interface bonding, making the dispersion of the carbon nanotubes in the coating more stable, reducing the shedding and migration of the carbon nanotubes, thereby improving the wear resistance of the coating.
[0021] The present invention uses tetraethyl orthosilicate to modify carbon nanotubes, so that tetraethyl orthosilicate is adsorbed in the pore structure of the carbon nanotubes, and the tetraethyl orthosilicate can be hydrolyzed to generate silicon oxide, thereby forming a uniform silicon oxide coating on the surface of the carbon nanotubes and constructing a microporous structure, which can effectively improve the bonding ability of the modified carbon nanotubes and fluorosilicone resin, thereby improving the wear resistance of the non-stick pan composite coating.
[0022] The present invention uses porous ceramic particles to sandblast the inner surface of the non-stick pan substrate to roughen the surface, significantly increase the surface area of the inner surface of the non-stick pan substrate, increase the contact area between the coating and the substrate, thereby increasing the bonding points between the coating and the non-stick pan substrate, thereby enhancing the physical bonding force between the coating and the substrate. At the same time, the roughening treatment can also increase the surface energy of the substrate surface, making it easier to interact with the coating material, further improving the bonding force. And the substrate surface after the roughening treatment is easier to penetrate and wet the coating material. The coating material can better penetrate into the tiny pores of the porous ceramic particles on the substrate surface to form a tighter combination. This improved penetration and wetting performance helps to improve the chemical bonding force between the coating and the substrate. DETAILED DESCRIPTION
[0023] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0024] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0025] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0026] Example 1
[0027] A method for preparing a non-stick pan composite coating comprises the following steps:
[0028] S1. Use porous ceramic particles to roughen the inner surface of the non-stick pan substrate by sandblasting, and then remove oil and clean it. The porous ceramic particles are prepared by the following method: kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate are mixed, stirred at 500rpm for 20min, and then placed in a granulator to make a size of 600nm, then placed in a drying oven, dried at 100℃ for 10h, and then placed in a sintering furnace and sintered at 1000℃ for 7h. The mass volume ratio of kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate is g / mL4.0:1.0:1.0:0.5:0.1:0.1:0.03.
[0029] S2, polytetrafluoroethylene powder and modified carbon nanotubes are mixed in a mass ratio of 1.0:0.1, and a composite powder with a particle size of 100nm is obtained by ball milling under a nitrogen atmosphere. The modified carbon nanotubes are prepared by the following method: the carbon nanotubes are soaked in tetraethyl orthosilicate at 40°C for 30min, separated by suction filtration, and dried at 60°C for 6h to obtain a modified intermediate. The mass volume ratio of carbon nanotubes to tetraethyl orthosilicate g / mL is 0.1:1.0. The modified intermediate is mixed with nano-alumina, placed in boiling water, boiled in boiling water for 30min and then cooled to room temperature, separated by suction filtration, and dried at 60°C for 6h to obtain a modified carbon nanotube. The mass volume ratio of the modified intermediate, nano-alumina, and boiling water g / mL is 1.0:0.1:2.0.
[0030] S3, put the composite powder into the silane coupling agent activation solution, ultrasonically mix for 15 minutes at 50°C, ultrasonic power 300W, and ultrasonic frequency 20kHz, then separate the composite powder, dry it at 60°C for 4 hours, and obtain the activated composite powder. The mass volume ratio of the composite powder to the silane coupling agent activation solution is 1:2. Put the activated composite powder into the fluorosilicone resin, add the diluent, stir and mix at 500rpm for 20 minutes to obtain the composite resin. The mass volume ratio of the activated composite powder, fluorosilicone resin, and diluent is 1.0:1.0:0.1. Among them, the diluent is composed of N,N-dimethylformamide and isopropanol in a volume ratio of 8:1. The silane coupling agent is γ-aminopropyl triethoxysilane. The silane coupling agent activation solution is prepared by diluting the γ-aminopropyl triethoxysilane 4 times with deionized water. The fluorosilicone resin is polytrifluoropropyl methylsiloxane.
[0031] S4. Coating the composite resin on the inner surface of the non-stick pan substrate and curing at 240° C. for 3 hours to obtain a non-stick pan composite coating.
[0032] The non-stick pan composite coating prepared by the above-mentioned preparation method of the non-stick pan composite coating has a thickness of 100 um.
[0033] Example 2
[0034] A method for preparing a non-stick pan composite coating comprises the following steps:
[0035] S1. Use porous ceramic particles to roughen the inner surface of the non-stick pan substrate by sandblasting, and then remove oil and clean it. The porous ceramic particles are prepared by the following method: kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate are mixed, stirred at 500rpm for 20min, and then placed in a granulator to make a size of 600nm, then placed in a drying oven, dried at 100℃ for 10h, and then placed in a sintering furnace and sintered at 1000℃ for 7h. The mass volume ratio of kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate is g / mL6.0:3.0:3.0:1.5:-0.3:0.2:0.05.
[0036] S2, polytetrafluoroethylene powder and modified carbon nanotubes are mixed in a mass ratio of 1.0:0.2, and a composite powder with a particle size of 100nm is obtained by ball milling under an argon atmosphere. The modified carbon nanotubes are prepared by the following method: the carbon nanotubes are soaked in tetraethyl orthosilicate at 40°C for 30min, separated by suction filtration, and dried at 60°C for 6h to obtain a modified intermediate. The mass volume ratio of carbon nanotubes to tetraethyl orthosilicate g / mL is 0.5:3.0. The modified intermediate is mixed with nano-alumina, placed in boiling water, boiled in boiling water for 30min and then cooled to room temperature, separated by suction filtration, and dried at 60°C for 4-6h to obtain a modified carbon nanotube. The mass volume ratio of the modified intermediate, nano-alumina, and boiling water g / mL is 1.0:0.2:3.0.
[0037] S3, put the composite powder into the silane coupling agent activation solution, ultrasonically mix for 15 minutes at 50°C, ultrasonic power 300W, and ultrasonic frequency 20kHz, then separate the composite powder, dry it at 60°C for 4 hours, and obtain the activated composite powder. The mass volume ratio of the composite powder to the silane coupling agent activation solution is 1:4 g / mL. Put the activated composite powder into fluorosilicone resin, add diluent, stir and mix at 500rpm for 20 minutes to obtain a composite resin. The mass volume ratio of the activated composite powder, fluorosilicone resin, and diluent is 1.0:1.2:0.2 g / mL. The diluent is composed of N,N-dimethylformamide and isopropanol in a volume ratio of 9:2. The silane coupling agent is a 1:1 combination of γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane. The silane coupling agent activation solution is prepared by diluting the silane coupling agent 6 times with deionized water. The fluorosilicone resin is polymethyltrifluoropropylsiloxane.
[0038] S4. Coating the composite resin on the inner surface of the non-stick pan substrate and curing at 240° C. for 3 hours to obtain a non-stick pan composite coating.
[0039] The non-stick pan composite coating prepared by the above-mentioned preparation method of the non-stick pan composite coating has a thickness of 200um.
[0040] Example 3
[0041] A method for preparing a non-stick pan composite coating comprises the following steps:
[0042] S1. Use porous ceramic particles to sandblast and roughen the inner surface of the non-stick pan substrate, and perform degreasing and cleaning. The porous ceramic particles are prepared by the following method: kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate are mixed, stirred at 750rpm for 15min, and then placed in a granulator to make a size of 700nm, then placed in a drying oven, dried at 125℃ for 9h, and then placed in a sintering furnace and sintered at 1150℃ for 5h. The mass volume ratio of kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate is g / mL5.0:2.0:2.0:1.0:0.2:0.15:0.04.
[0043] S2. Mix polytetrafluoroethylene powder and modified carbon nanotubes in a mass ratio of 1:0.15, and grind by ball milling in a helium atmosphere to obtain a composite powder with a particle size of 150nm. The modified carbon nanotubes are prepared by the following method: soak the carbon nanotubes in ethyl orthosilicate at 50°C for 25min, separate by suction filtration, and dry at 70°C for 5h to obtain a modified intermediate. The mass volume ratio of carbon nanotubes to ethyl orthosilicate g / mL is 0.3:2.0. Mix the modified intermediate with nano-alumina, put it in boiling water, boil it in boiling water for 35min and then cool it to room temperature, separate by suction filtration, and dry it at 70°C for 5h to obtain a modified carbon nanotube. The mass volume ratio of the modified intermediate, nano-alumina, and boiling water g / mL is 1.0:0.15:2.5.
[0044] S3, put the composite powder into the silane coupling agent activation solution, ultrasonically mix for 12.5 minutes at 55°C, ultrasonic power 400W, and ultrasonic frequency 35kHz, then separate the composite powder, dry it at 70°C for 3 hours, and obtain the activated composite powder. The mass volume ratio of the composite powder to the silane coupling agent activation solution is 1:3 g / mL. Put the activated composite powder into fluorosilicone resin, add diluent, stir and mix at 750rpm for 15 minutes to obtain a composite resin. The mass volume ratio of the activated composite powder, fluorosilicone resin, and diluent is 1.0:1.1:0.15 g / mL. The diluent is composed of N,N-dimethylformamide and isopropanol in a volume ratio of 8.5:1.5. The silane coupling agent is a 1:1:1 combination of γ-methacryloxypropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. The silane coupling agent activation solution is prepared by diluting the silane coupling agent by 5 times with deionized water. The fluorosilicone resin is polymethyl trifluoropropyl siloxane.
[0045] S4, coating the composite resin on the inner surface of the non-stick pan substrate and curing it at 250° C. for 2.5 hours to obtain a non-stick pan composite coating.
[0046] The non-stick pan composite coating prepared by the above-mentioned preparation method of the non-stick pan composite coating has a thickness of 150 um.
[0047] Example 4
[0048] A method for preparing a non-stick pan composite coating comprises the following steps:
[0049] S1. Use porous ceramic particles to sandblast and roughen the inner surface of the non-stick pan substrate, and then remove oil and clean it. The porous ceramic particles are prepared by the following method: kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate are mixed, stirred at 1000rpm for 10min, and then placed in a granulator to make a size of 800nm, then placed in a drying oven, dried at 150℃ for 8h, and then placed in a sintering furnace and sintered at 1300℃ for 5h. The mass volume ratio of kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate is g / mL4.0:1.0:1.0:0.5:0.1:0.1:0.03.
[0050] S2, polytetrafluoroethylene powder and modified carbon nanotubes are mixed in a mass ratio of 1.0:0.1, and a composite powder with a particle size of 200nm is obtained by ball milling under a nitrogen atmosphere. The modified carbon nanotubes are prepared by the following method: the carbon nanotubes are soaked in 60°C tetraethyl orthosilicate for 20min, separated by suction filtration, and dried at 80°C for 4h to obtain a modified intermediate. The mass volume ratio of carbon nanotubes to tetraethyl orthosilicate g / mL is 0.1:1.0. The modified intermediate is mixed with nano-alumina, placed in boiling water, boiled in boiling water for 40min and then cooled to room temperature, separated by suction filtration, and dried at 80°C for 4h to obtain a modified carbon nanotube. The mass volume ratio of the modified intermediate, nano-alumina, and boiling water g / mL is 1.0:0.1:2.0.
[0051] S3. Put the composite powder into the silane coupling agent activation solution, ultrasonically mix for 10 minutes at 60°C, ultrasonic power 500W, and ultrasonic frequency 50kHz, then separate the composite powder and dry it at 80°C for 2 hours to obtain the activated composite powder. The mass volume ratio of the composite powder to the silane coupling agent activation solution is 1:2. Put the activated composite powder into the fluorosilicone resin, add the diluent, stir and mix at 1000rpm for 10 minutes to obtain the composite resin. The mass volume ratio of the activated composite powder, fluorosilicone resin, and diluent is 1.0:1.0:0.1. The diluent is composed of N,N-dimethylformamide and isopropanol in a volume ratio of 8:1. The silane coupling agent is γ-mercaptopropyl triethoxysilane. The silane coupling agent activation solution is prepared by diluting γ-mercaptopropyl triethoxysilane 4 times with deionized water. The fluorosilicone resin is polytrifluoropropyl methylsiloxane or polymethyl trifluoropropyl siloxane.
[0052] S4, coating the composite resin on the inner surface of the non-stick pan substrate and curing at 260° C. for 2 hours to obtain a non-stick pan composite coating.
[0053] The non-stick pan composite coating prepared by the above-mentioned preparation method of the non-stick pan composite coating has a thickness of 200um.
[0054] Example 5
[0055] A method for preparing a non-stick pan composite coating comprises the following steps:
[0056] S1. Use porous ceramic particles to sandblast and roughen the inner surface of the non-stick pan substrate, and perform degreasing and cleaning. The porous ceramic particles are prepared by the following method: kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate are mixed, stirred at 1000rpm for 10min, and then placed in a granulator to make a size of 800nm, then placed in a drying oven, dried at 150℃ for 8h, and then placed in a sintering furnace and sintered at 1300℃ for 5h. The mass volume ratio of kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol, and sodium hexametaphosphate is g / mL6.0:3.0:3.0:1.5:0.3:0.2:0.05.
[0057] S2, polytetrafluoroethylene powder and modified carbon nanotubes are mixed in a mass ratio of 1.0:0.2, and a composite powder with a particle size of 200nm is obtained by ball milling in a helium atmosphere. The modified carbon nanotubes are prepared by the following method: the carbon nanotubes are soaked in 60°C tetraethyl orthosilicate for 20min, separated by suction filtration, and dried at 80°C for 4h to obtain a modified intermediate. The mass volume ratio of carbon nanotubes to tetraethyl orthosilicate g / mL is 0.5:3. The modified intermediate is mixed with nano-alumina, placed in boiling water, boiled in boiling water for 40min and then cooled to room temperature, separated by suction filtration, and dried at 80°C for 4h to obtain a modified carbon nanotube. The mass volume ratio of the modified intermediate, nano-alumina, and boiling water g / mL is 1.0:0.2:3.0.
[0058] S3. Put the composite powder into the silane coupling agent activation solution, ultrasonically mix for 10 minutes at 60°C, ultrasonic power 500W, and ultrasonic frequency 50kHz, then separate the composite powder and dry it at 80°C for 2 hours to obtain the activated composite powder. The mass volume ratio of the composite powder to the silane coupling agent activation solution is 1:4 g / mL. Put the activated composite powder into fluorosilicone resin, add diluent, stir and mix at 1000rpm for 10 minutes to obtain a composite resin. The mass volume ratio of the activated composite powder, fluorosilicone resin, and diluent is 1.0:1.2:0.2 g / mL. The diluent is composed of N,N-dimethylformamide and isopropanol in a volume ratio of 9:2. The silane coupling agent is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. The silane coupling agent activation solution is prepared by diluting β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane 6 times with deionized water. The fluorosilicone resin is polymethyltrifluoropropylsiloxane.
[0059] S4, coating the composite resin on the inner surface of the non-stick pan substrate and curing at 260° C. for 2 hours to obtain a non-stick pan composite coating.
[0060] The non-stick pan composite coating prepared by the above-mentioned preparation method of the non-stick pan composite coating has a thickness of 100 um.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 3 is that in step S1, unmodified carbon nanotubes of equal mass are used to replace the modified carbon nanotubes, and the modification of the carbon nanotubes in step S2 is not performed.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 3 is that in step S2, an equal volume of tetramethylsilane is used instead of ethyl orthosilicate to modify the carbon nanotubes.
[0065] Comparative Example 3
[0066] Compared with Example 3, the difference between this comparative example and Example 3 is that in step S2, the modified carbon nanotubes are prepared by the following method: the carbon nanotubes are immersed in tetraethyl orthosilicate at 60°C for 20 minutes, separated by suction filtration, washed with ethanol, and dried at 80°C for 4 hours to obtain the modified carbon nanotubes. The mass volume ratio of the carbon nanotubes to tetraethyl orthosilicate is 0.1:1.0 g / mL.
[0067] Comparative Example 4
[0068] The difference between this comparative example and Example 3 is that in step S3, no silane coupling agent is used to activate the composite powder. That is, the composite powder is directly put into the fluorosilicone resin, a diluent is added, and the mixture is stirred at 1000 rpm for 10 minutes to obtain a composite resin.
[0069] Non-stick and wear resistance testing
[0070] The non-stick pan composite coatings prepared in Examples 1-5 and Comparative Examples 1-4 were tested for non-stickiness and wear resistance, and the results are recorded in Table 1. The non-stickiness test method for non-stickiness was referred to in "GB / T 32095.2-2015 Performance and Test Specification of Non-stick Surface of Metal Cooking Utensils for Household Food", and the non-stickiness test for fried eggs and the non-stickiness test for baked bread were respectively carried out. The wear resistance was referred to in "GB / T 32095.2-2015 Performance and Test Specification of Non-stick Surface of Metal Cooking Utensils for Household Food", and the non-stick pans formed with the non-stick pan composite coating were respectively tested for plane wear resistance on a wear resistance testing machine, and the plane wear resistance cycle number when the composite coating had a wear mark with a width of more than 1 mm on the exposed pan surface or 10 linear wear marks with a length of more than 2 mm were recorded.
[0071] Table 1
[0072]
[0073]
[0074] As can be seen from Table 1, the non-stick pan composite coatings prepared in Examples 1 to 5 have excellent non-stick properties and wear resistance. Among them, Example 3 has the best performance.
[0075] Compared with comparative example 1, by embodiment 3, the dispersion performance of carbon nanotubes can be improved after modification, thereby suppressing the agglomeration of carbon nanotubes, so that carbon nanotubes can be evenly distributed with polytetrafluoroethylene powder, avoiding microscopic protrusions and depressions formed by agglomeration, and making the coating surface smoother. The smooth coating surface reduces the mechanical locking effect when in contact with food, reduces the possibility of food adhesion, and thus improves the non-stick performance of the coating. After modification, the surface roughness of carbon nanotubes can be improved, thereby increasing the contact area between carbon nanotubes and fluorosilicone resin, providing more binding sites, thereby enhancing the interface bonding, making the dispersion of carbon nanotubes in the coating more stable, reducing the shedding and migration of carbon nanotubes, thereby improving the wear resistance of the coating. During the curing process, fluorosilicone resin may undergo a cross-linking reaction to form a more solid network structure. The introduction of silanol groups on the surface of the modified carbon nanotubes can form chemical bonds with fluorosilicone resin, further enhancing the interfacial bonding between carbon nanotubes and fluorosilicone resin. Thereby improving the wear resistance of the coating.
[0076] By comparing Example 3 with Comparative Example 2, after surface treatment with ethyl orthosilicate, the ethyl orthosilicate adsorbed in the pore structure of the carbon nanotubes can be hydrolyzed to generate silicon oxide, forming a uniform silicon oxide coating on the surface of the carbon nanotubes and constructing a microporous structure, which can effectively improve the bonding ability between the modified carbon nanotubes and the fluorosilicone resin, thereby improving the wear resistance of the non-stick pan composite coating.
[0077] By comparing Example 3 with Comparative Example 3, after further modification of nano-alumina, nano-alumina can be adsorbed on the surface of the modified intermediate, thereby enhancing the surface strength and wear resistance of the non-stick pan composite coating. In addition, by mixing in boiling water, the activity of various substances can be effectively improved. At the same time, the high temperature and fluidity of boiling water may help improve the dispersibility of the modified intermediate, making it evenly distributed, and promoting the loading of nano-alumina on the surface of the modified intermediate. Mixing in boiling water also promotes further condensation and cross-linking of the silicon oxide layer on the surface of the modified intermediate, forming a more stable and wear-resistant structure, thereby enhancing the stability and wear resistance of the modified carbon nanotubes in the composite coating.
[0078] Compared with Comparative Example 4 by Example 3, the silane molecules in the silane coupling agent activation solution can react chemically with the active groups on the surface of polytetrafluoroethylene and modified carbon nanotubes in the composite powder to form a strong chemical bond, thereby significantly enhancing the interfacial bonding force between the composite powder and the fluorosilicone resin matrix, making the coating more tough and difficult to peel off. And the silane coupling agent can reduce the surface tension of the composite powder in the fluorosilicone resin, making it easier to disperse and evenly distribute, helping to reduce the agglomeration phenomenon in the coating, and improving the overall uniformity and consistency of the coating. In addition, the organosilicon component in the silane coupling agent can form a dense protective film on the surface of the coating, effectively blocking the external environment, such as the erosion of moisture, oxygen, etc., can significantly improve the weather resistance of the coating, and extend the service life of the non-stick pan. In addition, after the activation treatment of the silane coupling agent, the modified carbon nanotubes in the composite powder can be more firmly embedded in the fluorosilicone resin matrix, so that the excellent wear resistance of the modified carbon nanotubes can be effectively exerted, thereby significantly improving the wear resistance of the coating.
[0079] In order to further verify the bonding ability between the non-stick pan composite coating prepared by the present invention and the non-stick pan substrate, comparative examples 4 and 5 were set up to verify the bonding strength.
[0080] Comparative Example 4
[0081] Compared with Example 3, the difference between this comparative example and Example 3 is that the method for preparing a non-stick pan composite coating does not perform step S1, that is, the non-stick pan substrate is not sandblasted and roughened using porous ceramic particles.
[0082] Comparative Example 5
[0083] The difference between this comparative example and Example 3 is that in step S1, the raw materials for preparing the porous ceramic particles do not contain starch.
[0084] Binding strength test
[0085] The non-stick pans prepared in Example 3 and Comparative Examples 4-5 were placed on the workbench of the scratch tester, and they were fastened, with the scratch needle perpendicular to the non-stick pan coating. The scratch tester was started, the scratch speed was set to 5 mm / min, the loading rate was set to increase by 10 N per minute, and the scratch length was set to 10 cm. The scratch operation was performed according to the above parameters until the coating peeled off, and the load value when the coating peeled off was recorded. The examples and comparative examples were tested 5 times each, and the average values were recorded in Table 2.
[0086] Table 2
[0087] Example 3 Comparative Example 4 Comparative Example 5 Binding force / N 65 41 53
[0088] In the present invention, the inner surface of the non-stick pan substrate is sandblasted and roughened by using porous ceramic particles, which significantly increases the surface area of the inner surface of the non-stick pan substrate, increases the contact area between the coating and the substrate, thereby increasing the bonding points between the coating and the non-stick pan substrate, thereby enhancing the physical bonding force between the coating and the substrate. At the same time, the roughening treatment can also increase the surface energy of the substrate surface, making it easier to interact with the coating material, further improving the bonding force. In addition, the sandblasting roughening treatment will form tiny uneven structures on the substrate surface, which can form mechanical bites when the coating is applied, can effectively prevent the coating from falling off or peeling off during use, and improve the durability and stability of the coating. And the substrate surface after the roughening treatment is easier to penetrate and wet the coating material. The coating material can better penetrate into the tiny pores of the porous ceramic particles on the substrate surface to form a tighter combination. This improved penetration and wetting performance helps to improve the chemical bonding force between the coating and the substrate.
[0089] In the present invention, starch is added to the raw materials. When the raw material mixture is placed in a sintering furnace, as the temperature rises, the starch begins to pyrolyze and generate gas. These gases form bubbles inside the ceramic particles and gradually escape during the sintering process, leaving pores, thereby forming porous ceramic particles. When the pore structure of the porous ceramic particles is formed on the inner surface of the non-stick pan matrix, more mechanical bite points are provided. When the coating material is coated on these porous particles, they can penetrate deeper into the pores, forming a stronger mechanical bite, thereby enhancing the bonding force of the coating.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a non-stick pan composite coating, characterized in that: The following steps are involved: S1. Sandblasting the inner surface of the non-stick pan substrate with porous ceramic particles, and performing degreasing and cleaning processes; S2, mixing and grinding polytetrafluoroethylene powder and modified carbon nanotubes to obtain composite powder; S3, using a silane coupling agent to activate the composite powder, and adding the activated composite powder into a fluorosilicone resin to mix, so as to obtain a composite resin; S4, coating the composite resin on the inner surface of the non-stick pan substrate and curing the composite resin to obtain a non-stick pan composite coating; The porous ceramic particles in S1 are prepared by the following method: kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol and sodium hexametaphosphate are mixed, stirred at 500-1000rpm for 10-20min, and then placed in a granulator to make a size of 600-800nm, and then placed in a drying oven and dried at 100-150℃ for 8-10h, and then placed in a sintering furnace and sintered at 1000-1300℃ for 5-7h; the mass volume ratio of kaolin powder, alumina powder, silica powder, calcium carbonate powder, starch, polyvinyl alcohol and sodium hexametaphosphate is g / mL(4.0-6.0):(1.0-3.0):(1.0-3.0):(0.5-1.5):(0.1-0.3):(0.1-0.2):(0.03-0.05).
2. The method for preparing a non-stick pan composite coating according to claim 1, characterized in that: The modified carbon nanotubes in S2 are prepared by the following method: soaking carbon nanotubes in tetraethyl orthosilicate, then separating and drying to obtain a modified intermediate; then mixing the modified intermediate with nano-alumina in boiling water, then separating and drying to obtain the modified carbon nanotubes.
3. The method for preparing a non-stick pan composite coating according to claim 2, characterized in that: The carbon nanotubes are immersed in tetraethyl orthosilicate at 40-60° C. for 20-30 minutes, separated by suction filtration, and dried at 60-80° C. for 4-6 hours to obtain a modified intermediate; the mass volume ratio of the carbon nanotubes to tetraethyl orthosilicate is (0.1-0.5) g / mL:(1.0-3.0).
4. The method for preparing a non-stick pan composite coating according to claim 3, characterized in that: The modified intermediate is mixed with nano-alumina and placed in boiling water, boiled in boiling water for 30-40 minutes and then cooled to room temperature, separated by suction filtration, and dried at 60-80°C for 4-6 hours to obtain modified carbon nanotubes; the mass volume ratio of the modified intermediate, nano-alumina and boiling water is 1.0:(0.1-0.2):(2.0-3.0) g / mL.
5. The method for preparing a non-stick pan composite coating according to claim 1, characterized in that: The composite powder in S2 is prepared by the following method: polytetrafluoroethylene powder and modified carbon nanotubes are mixed and ground in a mass ratio of 1.0:(0.1-0.2) to obtain the composite powder; the particle size of the composite powder is 100-200nm, and the polytetrafluoroethylene powder and modified carbon nanotubes are ball-milled in a non-oxidizing atmosphere.
6. The method for preparing a non-stick pan composite coating according to claim 1, characterized in that: The composite resin in S3 is prepared by the following method: putting the composite powder into a silane coupling agent activation solution, ultrasonically mixing for 10-15 minutes at 50-60°C, an ultrasonic power of 300-500W, and an ultrasonic frequency of 20-50kHz, then separating the composite powder, and drying it at 60-80°C for 2-4 hours to obtain an activated composite powder; the mass volume ratio of the composite powder to the silane coupling agent activation solution is 1:(2-4) g / mL; putting the activated composite powder into a fluorosilicone resin, adding a diluent, and stirring and mixing at 500-1000rpm for 10-20 minutes to obtain a composite resin; the mass volume ratio of the activated composite powder, fluorosilicone resin, and diluent is 1.0:(1.0-1.2):(0.1-0.2) g / mL; the diluent is composed of N,N-dimethylformamide and isopropanol in a volume ratio of (8-9):(1-2).
7. The method for preparing a non-stick pan composite coating according to claim 1, characterized in that: The silane coupling agent is one or a combination of γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane, and β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane; and the silane coupling agent activation solution is prepared by diluting the silane coupling agent by 4-6 times with deionized water.
8. The method for preparing a non-stick pan composite coating according to claim 1, characterized in that: The fluorosilicone resin is polytrifluoropropylmethylsiloxane or polymethyltrifluoropropylsiloxane.
9. The method for preparing a non-stick pan composite coating according to claim 1, characterized in that: The curing and molding in S4 is specifically curing and molding at 240-260° C. for 2-3 hours to obtain a non-stick pan composite coating.
10. The non-stick pan composite coating obtained by the method for preparing a non-stick pan composite coating according to any one of claims 1 to 9, characterized in that: The thickness of the non-stick pan composite coating is 100-200um.